Diagnostic Uncertainties: Chorea - Cincotta, Molly C.; Walker, Ruth H. (Seminars in Neurology, 2023)
Chorea is a hyperkinetic movement disorder with a multitude of potential etiologies, both acquired and inherited. Although the differential diagnosis for new-onset chorea is extensive, there are often clues in the history, exam, and basic testing that can help to narrow the options. Evaluation for treatable or reversible causes should take priority, as rapid diagnosis can lead to more favorable outcomes. While Huntington's disease is most common genetic cause of chorea, multiple phenocopies also exist and should be considered if Huntington gene testing is negative. The decision of what additional genetic testing to pursue should be based on both clinical and epidemiological factors. The following review provides an overview of the many possible etiologies as well as a practical approach for a patient presenting with new-onset chorea.
Keywords: chorea; Huntington's disease; Sydenham disease; hyperglycemic hemichorea/hemiballismus